2020
DOI: 10.1186/s12887-020-1997-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory infection and its associated factors among children under-five years attending pediatrics ward at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia: institution-based cross-sectional study

Abstract: Background: Acute respiratory infection is manifested by cough accompanied by short rapid breathing which may be associated with death especially when there are other co-morbidities. From an estimated 5.4 million children under -five years that died in 2017-roughly half of those deaths occurred in sub-Saharan Africa and acute respiratory infection contributed to the highest number of deaths. The current study aimed at evaluating the prevalence of, and risk factors associated with, acute respiratory infection h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
7
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 46 publications
3
59
7
6
Order By: Relevance
“…Some of the factors identified as influencing morbidity among children include maternal education, maternal age, child's nutritional status, child's age, household wealth, residence, handwashing, sanitation, water source, use of insecticide-treated nets and exposure to information on morbidity, among others. [6][7][8][9][10][11][12][13][14][15][16][17] For instance, some studies showed that diarrhoea infection is higher among children whose mothers have no education and do not wash their hands after using the toilet. Other studies revealed that malaria and acute respiratory infection are higher among children in rural setting and children whose mothers are 16-17 and 28-33 years of age.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Some of the factors identified as influencing morbidity among children include maternal education, maternal age, child's nutritional status, child's age, household wealth, residence, handwashing, sanitation, water source, use of insecticide-treated nets and exposure to information on morbidity, among others. [6][7][8][9][10][11][12][13][14][15][16][17] For instance, some studies showed that diarrhoea infection is higher among children whose mothers have no education and do not wash their hands after using the toilet. Other studies revealed that malaria and acute respiratory infection are higher among children in rural setting and children whose mothers are 16-17 and 28-33 years of age.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…In Ethiopia, there are 55 deaths per 1000 live births in children under-five due to acute respiratory infection, placing it among the world's highest mortality rates [19]. Prior studies indicated that maternal age, residence, maternal hand hygiene information [20], maternal literacy, smoking, use of animal dung as a fuel source, nutritional status [21], absence of a separate kitchen, and lack of windows were significantly associated with acute respiratory infections [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout 2017-2018 the number of children in the Besuki Agriculture area who had to be hospitalized due to ARI was 45%. This result is higher than the number of children with ARI in India (41.6%) (Savitha & Gopalakrishnan, 2018), Northern Ethiopia (27.3%) (Dagne et al, 2020).…”
Section: Health Problems Effect To Diseasementioning
confidence: 59%